Testicular apoptosis and proliferation in relation to body mass index and m-TESE success in nonobstructive azoospermic men - ŞİRVANCI, SERAP (My University, 2023)
Male infertility occurs due to the disruption of the balance of proliferation and apoptosis in the testicular tissue. It is important toshow the effect of increased body mass index, which is one of the factors that disrupts this balance of apoptosis and proliferation,not only at the blood hormone level but also at the tissue level. For this reason, the present study is aimed at demonstrating therelation between body mass index and cell turnover in the testis using immunohistochemical methods. In the present study,patients were grouped as normal, overweight and obese, and as m-TESE positive and negative. The sperm retrieval rate withmicrosurgical testicular sperm extraction (m-TESE) was 41.67%. Histological diagnosis of testicular tissues was made withhematoxylin and eosin and Masson’s trichrome staining. Apoptosis and proliferation in the testicular tissue were demonstratedby TUNEL and PCNA immunohistochemical methods, respectively. It was concluded that BMI had no significant effect onreproductive hormone profile (FSH, LH, and testosterone), m-TESE success, apoptosis, and proliferation in testicular tissue innonobstructive azoospermic men. In addition TUNEL positivity and proliferative index was found to be significantly correlatedwith testicular histology and m-TESE outcome.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine